Factors Influencing Online Brand Trust: Evidence from Online Buyers in Kathmandu Valley - Kharel, Bina (Journal of Business and Social Sciences Research, 2019)
This paper aims to identify the factors that influence consumers’ online purchasing behavior in the Kathmandu Valley and understand the relationship between trust and the independent factors of trust in their buying behavior. The analysis is descriptive in nature and focuses on hypothesis testing using structured questionnaire and interview to collect primary data from a sample size of 200 respondents focusing on jobholders, business people, students and housewives. The secondary data is taken based on reports, published articles, websites and journals. Results of the study indicate that a majority of the respondents believe trust is an important factor for online purchase. Though some of the respondents feel that time-saving is one of the important factors for purchasing online, 56 percent of the respondents prefer to shop online only three times a year. The study also shows that the maximum number of respondents prefer buying tickets more than any other commodity online. Even though priority has been given to brand reputation, respondents did not find information as an important factor influencing an online purchasing decision.